Development of Local Potential-Based Exploration Modules for Learning About Terrestrial Insect Diversity in High Schools - Nugroho, Anwari Adi; Armania, Vallery; Abdildauly, Alem (Biosfer: Jurnal Tadris Biologi, 2026)
This study aimed to analyze terrestrial insect diversity and develop a local potential-based exploration module for high school biology learning aligned with the Merdeka Curriculum. The research employed a Research and Development (R&D) design adapted from the Borg and Gall model, consisting of biodiversity data collection, module design, expert validation, and limited field testing. Field observations conducted at the Integrated Agricultural Laboratory of Jagan, Sukoharjo recorded 641 terrestrial insect individuals with a moderate level of species diversity and a relatively stable ecological structure. These empirical data were transformed into structured learning materials incorporating exploration activities, guided inquiry, and reflective tasks. The developed module was validated by subject-matter experts, instructional design experts, biology teachers, and Grade X students. The validation results indicated a very high level of feasibility, with expert scores exceeding 87% and positive responses from both teachers and students in terms of clarity, relevance, readability, and usability. These findings suggest that integrating authentic local biodiversity data into instructional modules enhances the quality and meaningfulness of biology learning. The module also demonstrates strong potential for adaptation in other regions through contextualization based on local biodiversity resources. Pengembangan Modul Eksplorasi Berbasis Potensi Lokal untuk Pembelajaran Keanekaragaman Serangga Darat di Sekolah Menengah Atas ABSTRAK: Penelitian ini bertujuan untuk menganalisis keanekaragaman serangga darat serta mengembangkan modul eksplorasi berbasis potensi lokal untuk pembelajaran biologi SMA yang selaras dengan Kurikulum Merdeka. Penelitian menggunakan desain Research and Development  yang diadaptasi dari model Borg dan Gall, meliputi pengumpulan data biodiversitas, perancangan modul, validasi ahli, dan uji coba terbatas. Hasil observasi lapangan di Laboratorium Pertanian Terpadu Jagan, Sukoharjo mencatat 641 individu serangga darat dengan tingkat keanekaragaman sedang dan struktur ekologi yang relatif stabil. Data empiris tersebut kemudian diintegrasikan ke dalam bahan ajar yang memuat aktivitas eksplorasi, penyelidikan terbimbing, dan refleksi. Modul yang dikembangkan divalidasi oleh ahli materi, ahli desain pembelajaran, guru biologi, dan siswa kelas X. Hasil validasi menunjukkan tingkat kelayakan yang sangat tinggi, dengan skor ahli di atas 87% serta respons positif dari guru dan siswa terkait kejelasan, relevansi, keterbacaan, dan kegunaan. Temuan menunjukkan integrasi data keanekaragaman hayati lokal dalam modul pembelajaran mampu meningkatkan kualitas dan kebermaknaan serta dimanfaatkan di berbagai daerah berbasis potensi lokal.